ANEMIA IN CHRONIC RENAL FAILURE - Butt, Muhammad Luqman; Shaft, Tahir; Moinuddin, Moinuddin; Rahman, Aziz urr (Journal of Ayub Medical College Abbottabad, 1999)
Anaemia in chronic renal failure (CRF) is almost universal abnormality. Sixty diagnosed cases of i. ’RF were included in this study which included patients of peritoneal and haemodialysis. anemia of variable degree was present in almost all the patients and its incidence was same in both groups. The mean pre-dialysis haemoglobin (lib) was 7.4 g dl. After dialysis slight increase in HB occurred, the increase was more in, patients on haemodialysis. The postdialysis mean lib level was S.3 g dl. Similar changes occurred in R.B(count and packed cell Volume (PVC). The predialysis sample in IS. 13% showed reticulocytosis and the mean Retie. Count was 1.5%. Vo changes in mean Retie count occur after dialysis. The presence of burr cells and fragmented RBC was the commonest red cells morphological abnormality observed in our patents. Dialysis in any form has no wholesome effect on morphological abnormalities. Anaemia of CRF persists and despite treatment remain significantly anemic.